1995
DOI: 10.1016/s0006-3495(95)80435-2
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer spectroscopy on nonequilibrium states of myoglobin: a study of r-t relaxation

Abstract: A frozen solution of 57Fe-enriched metmyoglobin was irradiated by x rays at 77 K. Mössbauer spectra showed a reduction of Fe(III) high spin by thermalized electrons and a production of a metastable Fe(II) low spin myoglobin complex with H2O at its sixth coordination site. The relaxation of the intermediate was investigated by Mössbauer spectroscopy as a function of temperature and time. The relaxation process starts above 140 K and is fully completed at approximately 200 K. At temperatures between 140 and 200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 17 publications
4
49
0
1
Order By: Relevance
“…Spectroscopic investigations have shown that Xe1 is the primary sink of CO at temperatures above the characteristic temperature where protein dynamics becomes important (29). Taking into account low-and high-temperature dynamics studies on Mb (3,5,52) and relating them to our time-resolved results at room temperature, we propose that two fundamental processes are responsible for CO migration in Mb. (i) Protein dynamics enables structural f luctuations and transiently opens and closes channels for the CO to migrate to positions where it is trapped effectively.…”
Section: Events Faster Than Our Experimental Time Resolution: Subnanomentioning
confidence: 66%
“…Spectroscopic investigations have shown that Xe1 is the primary sink of CO at temperatures above the characteristic temperature where protein dynamics becomes important (29). Taking into account low-and high-temperature dynamics studies on Mb (3,5,52) and relating them to our time-resolved results at room temperature, we propose that two fundamental processes are responsible for CO migration in Mb. (i) Protein dynamics enables structural f luctuations and transiently opens and closes channels for the CO to migrate to positions where it is trapped effectively.…”
Section: Events Faster Than Our Experimental Time Resolution: Subnanomentioning
confidence: 66%
“…DFT calculations have shown that the Fe-O distance will increase by 0.1 Å when the Fe IV -OH goes from being a donor to becoming an acceptor of a hydrogen bond to the distal His (48 Resting State -In the 1970s Gasyna (130) showed that ferric Mb can be one-electron reduced by radiolysis of 60 Co at 77 K. This is the same effect that we observed for our ferric Mb crystals and that Engler et al (131) observed after x-ray exposure. A reduction at low temperature 77-110 K probably reduces the Fe III to Fe II , but at this temperature the water that ligates to the iron will not be able to move away to generate the normal ferrous deoxy state (132,133). The intermediate state is most probably a low spin (S ϭ 0) ferrous Fe II -H 2 O or Fe II -OH state.…”
Section: Discussionmentioning
confidence: 99%
“…A very recent and thorough survey on cryoradiolytic reduction of crystalline heme proteins has demonstrated a very fast reduction of ferric Mb (134), which confirms our observations. In frozen solutions the low spin ferrous intermediates relax to the normal high spin ferrous deoxy Mb during heating (132,133). When we carried out a short annealing of this state in crystals it was the high spin ferric Mb state that was regenerated and not the ferrous deoxy state.…”
Section: Discussionmentioning
confidence: 99%
“…7. The experiments have been analyzed by a simple model where a distributed energy barrier had to be surmounted for structural relaxation [41].…”
Section: The Functional Relevance Of Slow Quasidiffusive Motionsmentioning
confidence: 99%